Cryopreservation in Blastocyst Stage Effectively Reduce the Number of Embryos Cryopreserved [la Criopreservación Embrionaria en Estadios Más Avanzados de Desarrollo Disminuye la Frecuencia de Pacientes Con Embriones Criopreservados y el Número de Embriones Criopreservados] - Schwarze-Meza, J (2012)
Background: Multiple pregnancies are the main complication associated to assisted reproduction, due to the transfer of more than one embryo. Embryo cryopreservation allows the sequential transfer of all generated embryos, thus diminishing the risk of multiple pregnancies. However, it leads to accumulation of cryopreserved embryos. To reduce their accumulation in our unit, we started to preserve embryos as blastocysts, that have a rate of successful pregnancies of approximately 40%. Aim: To perform a sensitivity analysis of this change of policy on the accumulation of embryos. Material and Methods: Records of 571 cycles of in vitro fertilization since 2007 were reviewed, assuming a transference rate of two embryos in women aged less than 35 years and three embryos in older women. The number of embryos that would be preserved as zygotes, eight cell stage or blastocysts, was analyzed. Results: Multiple component logistic regression analysis showed a 20% reduction in the odds ratio of cryopreservation per year of age. There was a 95% reduction in the ratio, when comparing the preservation of third and first day embryos and a 99% reduction when comparing preservation of embryos in blastocyst stage and first day embryos. Conclusions: Cryopreservation at blastocyst stage effectively decreased the frequency of embryo cryopreservation.